Pemanfaatan E-Commerce Pada Penjualan Produk Usaha Asinan Myesha Di Kota Kendari - Siama, Romi Apriadi; Nuryadi, Ahmad Muhlis; Rosmalah, Sitti (Media Agribisnis, 2023)
This study aims to determine the use of e-commerce in product sales Myesha pickled business in kendari city. This research was conducted from June to July 2023. The data used in this study is primary data obtained by conducting interview directly with the owner of the Myesha Asinan business. Method of collecting data In this study using a survey method. The analytical method used in this research is a descriptive method with a quantitative approach, to describe sales Asinan Myesha business products in utilizing e-commerce. The results of the research show that the benefits of e-commerce in selling Asinan Myesha business products, that is, can help expand market reach, increase brand awareness, make it easy for customers to make purchases, save costs, manage shipments more easily, and can help increase the number of orders and sales turnover. Keywords: utilization, e-commerce, sales, business, pickles